2021
DOI: 10.1002/adom.202101191
|View full text |Cite
|
Sign up to set email alerts
|

Phase Enabled Circular Dichroism Reversal in Twisted Bi‐Chiral Propeller Metamolecule Arrays

Abstract: Artificial chiral structures play a crucial role in the realization of strong chiroptical responses and flexible light manipulation. Here, a unique bi‐chiral propeller metamolecule array is demonstrated in which the geometric chirality of the subunit with intracellular blades is opposite to that of the subunit with intercellular blades. Benefited from the special propeller twists, it is demonstrated that the propeller metamolecule arrays support the phase controlled chiral surface lattice resonances, whose amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Bichiral structures normally exhibit two CD responses with opposite signs at different wavelengths when consisting of two isolated chiral centers with opposite handedness. 61,62 Interestingly, the two chiral centers are not completely isolated from each other in our cases; their chiral units share the same twisted blade edge as marked with both red-and blue-dotted lines (Figure S7). Therefore, the CD responses of the overall plasmonic structure could be the results of the plasmon hybridization of two chiral units because they are intertwined and coupled with each other.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Bichiral structures normally exhibit two CD responses with opposite signs at different wavelengths when consisting of two isolated chiral centers with opposite handedness. 61,62 Interestingly, the two chiral centers are not completely isolated from each other in our cases; their chiral units share the same twisted blade edge as marked with both red-and blue-dotted lines (Figure S7). Therefore, the CD responses of the overall plasmonic structure could be the results of the plasmon hybridization of two chiral units because they are intertwined and coupled with each other.…”
Section: Resultsmentioning
confidence: 79%
“…Plasmonic structures with multiple chiral centers provide an interesting strategy to manipulate the sign of plasmonic CD. Chiral centers either left-handed (LH) or right-handed (RH) were used to help clarify the chirality of molecules with one or more chiral centers. It has been proposed and demonstrated that the concept of chiral centers can be transferred to the plasmonic analogs of chiral molecules. , Based on the plasmon hybridization theory, plasmonic diastereomers with reconfigurable CD were constructed by combining more than one chiral center through a DNA-based chiral assembly method. ,, More interestingly, by tuning the coupling and competition between two chiral centers with opposite handedness, the CD signal of the propeller meta-molecules array can be reversed without the inversion of the geometric chirality. , The propeller structure with bichiral centers was designed and fabricated by using a focused ion beam (FIB) based nanokirigami method . For chiral plasmonic NPs prepared by seed-mediated growth method, a single chiral center was proposed in most cases with the limitation of tuning the CD reversal. ,,,, How to create multiple chiral centers on an individual plasmonic NPs using wet chemical approaches, particularly the seed-mediated chiral growth method, remains a fundamentally intriguing open question.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prospects of these applications have triggered the study and characterization of a variety of periodic arrays supporting chiral lattice resonances. The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, , such as helices, or multiple nanostructures forming a chiral arrangement. , As expected, the lattice resonances supported by these systems exhibit different responses under illumination with right- and left-handed circularly polarized light. More recently, it has been shown that the combination of a rectangular lattice with an achiral unit cell results in arrays capable of supporting lattice resonances with some degree of chirality, which can be enhanced by positioning the array in an inhomogeneous dielectric environment .…”
Section: Introductionmentioning
confidence: 92%
“…53−55 The prospects of these applications have triggered the study and characterization of a variety of periodic arrays supporting chiral lattice resonances. 56−64 The majority of these arrays are built from the repetition of chiral unit cells, made of either individual nanostructures with complex chiral morphologies, [56][57][58]63 such as helices, 60 or multiple nanostructures forming a chiral arrangement. 65,66 circularly polarized light.…”
Section: ■ Introductionmentioning
confidence: 99%